Modern and traditional methods for measuring money supply: The case of Saudi Arabia - William A. Barnett; Ryadh M. Alkhareif (International Journal of Financial Studies, 2015)
This paper compares the "simple-sum" monetary aggregates (M1 and M2) published by the Saudi Arabian Monetary Agency (SAMA) with the new monetary aggregates (D1 and D2)-known as the Divisia monetary indexes. The former aggregates are constructed from a simple accounting identity, whereas the Divisia aggregates are constructed using statistical index number theory and aggregation theory. The findings suggest that both D1 and M1 are identical, given the perfect substitutability of the monetary components within those aggregates. For the broader monetary aggregates where perfect substitutability assumption is not realistic, the two monetary indexes differ substantially. SAMA could benefit by using both monetary indexes simultaneously to better monitor liquidity in the market.
Keywords: E41; E51; E52; E58; 330; monetary aggregation; Divisia monetary aggregates; index number theory